Rasionalisasi Relasi Keluarga sebagai Faktor Perceraian menurut Pasal 116 KHI dan Undang-Undang No. 1 Tahun 1974 - Najwa, Nailu (Universitas Islam DDI AG.H. Abdurrahman Ambo Dalle, 2026)
The rationalization of family relations is a social phenomenon that has developed within modern household life and is often used as a basis for filing for divorce. Changes in the mindset of married couples, which emphasize rational considerations such as personal interests, role efficiency, and the perceived benefits of the relationship, have influenced the sustainability of the household. This study aims to examine the rationalization of family relations as a factor in divorce, as viewed from Article 116 of the Compilation of Islamic Law (KHI) and Undang-Undang Nomor 1 Tahun 1974 on Marriage. The research was conducted using a normative juridical method, which focuses on the study of statutory regulations. The findings indicate that although the rationalization of family relations is not explicitly stated as a ground for divorce in either the KHI or the Marriage Law, its substance is reflected in legal reasons such as continuous disputes and ongoing conflicts, as well as the failure of husband and wife to fulfill their marital obligations. This study emphasizes that changes in family relational patterns require a functional understanding so that the application of divorce law remains aligned with the objectives of marriage. Therefore, grounds for divorce should not be understood merely in a formal sense as stipulated in the applicable regulations, but also by taking into account the psychological, social, and relational dynamics underlying the breakdown of the family.